Security of Employee Salary Data Using the ElGamal Algorithm By Utilizing the Diffie-Hellman Algorithm Key Generator - Indakholasy, Barru; Hara Pardede, Akim Manaor; Khair, Husnul (International Journal of Informatics, Economics, Management and Science; Vol 3 No 1 (2024): IJIEMS (January 2024)DO - 10.52362/ijiems.v3i1.1221, 2024)
Data security is something that is very important for companies or organizations, one of which is the South Binjai District Office. Almost all work in the South Binjai sub-district office uses a computer, especially in processing data stored in the form of data files on storage media without encoding. In today's digital era, many irresponsible parties find it easy to tap company data so that it can be easily accessed and there is also some software that can be easily used to crack passwords. One of the data that needs to be kept confidential is employee salary data. To overcome these problems, a security system is needed to secure text data. The cryptographic method is regarding encryption techniques in which plaintext is scrambled using an encryption key to become ciphertext which is applied in data security systems. The Diffie-Hellman algorithm is a key exchange algorithm, this algorithm is limited to the key exchange process, so it must require another algorithm for the encryption and decryption process such as the ElGamal algorithm. The use of these two algorithms can strengthen the level of data security. From the results of trials conducted, the sample data used containing the word "KARYAWAN" was successfully secured with both diffie-helman and ElGamal algorithms.